There's no place like home a comparative study on the socially constructed emotions, family relationship and family communication environment of adolescents who belong to a closely and non-closely knit family - Dotimas,Leonor Canizares; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The pursuit of the study followed the general assumption that, emotions of adolescents were socially constructed through family relationship and family communication environment. The primary key informants of the study were the adolescents and the secondary was the parents. They were from nuclear families. Moreover, the family was classified into two types namely: the closely and non-closely knit family. Its main thrust was to compare and contrast the socially constructed emotions of adolescents from both family structures. Thus, it used a case study design that was explanatory and exploratory in nature to gather the necessary data. Using a purposive sampling method, thirty-six Focused Interviews were handed over to the key informants. The instrument was used to probe responses and analyze findings of the study. The study revealed that not-all close relationship were nurturing and has a positive outcome. Otherwise, almost all were beneficial and contributes to effective functioning. On one hand, non-close relationship were not necessarily damaging and hindrance to effective functioning. Even though, relationship was not growth-producing and communication was characterized as a "close system", one-half of the adolescents have a positive emotions. The major factor affecting the emotions was the family. It plays an important role in the construction of emotions. Hence, different individuals were created from their family interaction.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Family relationships -- Philippines; Family structure -- Philippines